PENERAPAN EVALUASI MANAJEMEN PERAWATAN DENGAN METODE OVERALL EQUIPMENT EFFECTIVENESS (OEE) PADA HASIL PRODUKSI MESIN PACKING WAFER DI PT. XYZ: Array - Dermawansyah, Dermawansyah; Ritonga, Din Aswan Amran; Junaidi, Junaidi (Universitas Harapan Medan, 2020)
To produce according to production targets, of course supported by machines and equipment at every stage of the process and must be operated effectively and efficiently. operating machinery and equipment effectively and efficiently requires a good machine maintenance system. The research method used is Overall Equipment Effectiveness. After conducting the research, the average value of the Overall Equipment Effectiveness of the wafer is 34.00%. This result is still far from the world class standard of 85%. It is known that the biggest losses that cause the low OEE value are reduced speed losses by 143.3% and defect losses by 9.68% of the total losses. What causes low losses consists of factors such as machines, humans, environment, and methods. . To reduce these losses, the company should provide skills training and knowledge to operators about signs of damage to the equipment. In addition, operators are given additional work in the form of equipment maintenance that is often used at work so that maintenance work can be more focused. Then the company must pay more attention to operator comfort in working so that fatigue can be reduced and operator productivity increases and increases operator awareness of the equipment they use.